Tìm x, biết:
(23:4) . 2(x+1)=64
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 3:
a: Ta có: \(23\left(42-x\right)=23\)
\(\Leftrightarrow42-x=1\)
hay x=41
b: Ta có: 15(x-3)=30
nên x-3=2
hay x=5
Bài 1:
a: 32+89+68=100+89=189
b: 64+112+236=300+112=412
c: \(1350+360+650+40=2000+400=2400\)
a. 128 - 3 x (X + 2) = 23
3 x (X + 2) = 128 - 23
X + 2 = 105 : 3
X = 35 - 2
X = 33
b. (12 x X - 64) x 8 = 4,64
12 x X - 64 = 4,64 : 8
12 x X = 0,58 + 64
X = 64,58 : 12
X = \(\frac{3229}{600}\)
c. [(4 x X + 28) x 3 + 55] : 5 = 35
[(4 x X + 28) x 3 + 55] = 35 x 5
(4 x X + 28) x 3 = 175 - 55
4 x X + 28 = 120 : 3
4 x X = 40 - 28
X = 12 : 4
X = 3
d. 720 : [41 - (2 x X - 5)] = 8 x 5
41 - (2 x X - 5) = 720 : (8 x 5)
2 x X - 5 = 41 - 18
2 x X = 23 + 5
X = 28 : 2
X = 14
x nhỏ : dấu nhân
X lớn : X
a)\(x^{23}=64.x^{20}\)
\(\Leftrightarrow\frac{x^{23}}{x^{20}}=64\)
\(\Leftrightarrow x^3=64\Rightarrow x=4\)
b)\(\left(4x-3\right)^4=3-4x\)
\(\Leftrightarrow\left(3-4x\right)^4=3-4x\)
\(\Leftrightarrow\left(3-4x\right)^3=1\)
\(\Leftrightarrow3-4x=1\)
\(\Leftrightarrow x=\frac{1}{2}\)
a) \(2^x=8\)
⇔ \(2^x=2^3\)
⇒ \(x=3\)
b) \(3^x=27\)
⇔ \(3^x=3^3\)
⇒ \(x=3\)
c) \(\left(-\dfrac{1}{2}\right)x=\left(-\dfrac{1}{2}\right)^4\)
⇔ \(x=\left(-\dfrac{1}{2}\right)^4\div\left(-\dfrac{1}{2}\right)\)
⇔ \(x=\left(-\dfrac{1}{2}\right)^3\)
d) \(x\div\left(-\dfrac{3}{4}\right)=\left(-\dfrac{3}{4}\right)^2\)
⇔ \(x=\left(-\dfrac{3}{4}\right)^2\cdot\left(-\dfrac{3}{4}\right)\)
⇔ \(x=\left(-\dfrac{3}{4}\right)^3=-\dfrac{27}{64}\)
d) \(\left(x+1\right)^3=-125\)
⇔ \(\left(x+1\right)^3=\left(-5\right)^3\)
⇔ \(x+1=-5\)
⇔ \(x=-5-1=-6\)
2:
a: (x-1,2)^2=4
=>x-1,2=2 hoặc x-1,2=-2
=>x=3,2(loại) hoặc x=-0,8(loại)
b: (x-1,5)^2=9
=>x-1,5=3 hoặc x-1,5=-3
=>x=-1,5(loại) hoặc x=4,5(loại)
c: (x-2)^3=64
=>(x-2)^3=4^3
=>x-2=4
=>x=6(nhận)
=>(4-x:2)^3=1+2*(8-5)+1
=>(4-x:2)^3=2+2*3=8
=>4-x:2=2
=>x:2=2
=>x=4
Có: \(\frac{1}{4}.\frac{2}{6}.\frac{3}{8}.\frac{4}{10}...\frac{30}{62}.\frac{31}{64}=\frac{1}{2.2}.\frac{2}{2.3}.\frac{3}{2.4}...\frac{30}{2.31}.\frac{31}{2.32}=\frac{1}{2}.\frac{1}{2}.\frac{1}{2}...\frac{1}{2}.\frac{1}{2}.\frac{1}{32}\)
\(=\frac{1}{2^{31}.2^5}=\frac{1}{2^{36}}=2^x\)\(\Rightarrow1=2^x.2^{36}=2^{36+x}\)\(\Rightarrow2^{36+x}=2^0\Rightarrow36+x=0\Rightarrow x=-36\)
a: x^3=7^3
=>x^3=343
=>\(x=\sqrt[3]{343}=7\)
b: x^3=27
=>x^3=3^3
=>x=3
c: x^3=125
=>x^3=5^3
=>x=5
d: (x+1)^3=125
=>x+1=5
=>x=4
e: (x-2)^3=2^3
=>x-2=2
=>x=4
f: (x-2)^3=8
=>x-2=2
=>x=4
h: (x+2)^2=64
=>x+2=8 hoặc x+2=-8
=>x=6 hoặc x=-10
j: =>x-3=2 hoặc x-3=-2
=>x=1 hoặc x=5
k:
9x^2=36
=>x^2=36/9
=>x^2=4
=>x=2 hoặc x=-2
l:
(x-1)^4=16
=>(x-1)^2=4(nhận) hoặc (x-1)^2=-4(loại)
=>x-1=2 hoặc x-1=-2
=>x=3 hoặc x=-1
(23 : 4).2x + 1 = 64
23 : 22 . 2x + 1 = 64
2.2x + 1 = 26
2x + 2 = 26
x + 2 = 6
=> x = 4
Vậy x = 4